Globularity and language-readiness: generating new predictions by expanding the set of genes of interest - Boeckx, Cedric; Benítez-Burraco, Antonio (Frontiers in Psychology, 2014)
This study builds on the hypothesis put forth in Boeckx and Benitez-Burraco (2014), according to which the developmental changes expressed at the levels of brain morphology and neural connectivity that resulted in a more globular braincase in our species were crucial to understand the origins of our language-ready brain. Specifically, this paper explores the links between two well-known ‘language-related’ genes like FOXP2 and ROBO1 implicated in vocal learning and the initial set of genes of interest put forth in Boeckx and Benitez-Burraco (2014), with RUNX2 as focal point. Relying on the existing literature, we uncover potential molecular links that could be of interest to future experimental inquiries into the biological foundations of language and the testing of our initial hypothesis. Our discussion could also be relevant for clinical linguistics and for the interpretation of results from paleogenomics.